Nonlinear Control of Permanent Magnet Synchronous Generators (PMSG) Using Feedback Linearization and Sliding Mode Control (Sebha University Conference Proceedings, 2025)
Controlling  permanent  magnet  synchronous machines  (PMSM)  is  particularly  challenging  due  to  their nonlinear dynamics. Traditional linear controllers, such as PI and  PID,  perform  adequately  in  systems  with  constant parameters, but they often fall short when applied to nonlinear systems  with  variable  parameters,  lacking  the  necessary robustness. To address these limitations and achieve decoupled control  of  the  machine,  several  methods  have  been  proposed, with  robust  nonlinear  control  techniques  gaining  significant attention in power electronics and drive systems. Notable among these are sliding mode control (SMC) and nonlinear input output feedback linearization (IOFL). SMC is well-regarded for its exceptional dynamic performance in PMSM drives, offering high robustness and straight forward implementation in both software and hardware. However, its main limitation lies in the chattering phenomenon. In contrast, input-output linearization control demonstrates excellent behavior in both steady-state and dynamic regimes, while also providing effective decoupling of system variables.  This  article  synthesizes  two  control approaches—sliding  mode  control  and  feedback  linearization control  based  on  input-output  linearization—to  regulate  the speed  of  a  PMSM.  A comparative analysis conducted in Matlab/Simulink highlights the superior performance of the feedback linearization controller over SMC.